Inquérito sorológico de agentes infecciosos que afetam a reprodução de bovinos leiteiros em Minas Gerais, 2001 - 2002. - Paulo Artur Konrad (2003)
With the objective to determine the infection affecting the breeding of cattle in Minas Gerais, for possible association with reports of miscarriages and replications of heat occurring during the period 2001-2002, we carried out a seroepidemiological on 15 farms located in various regions of the state, whose herds had reproductive problems. Were searched for antibodies to brucellosis, leptpspiroses, bovine rhinotracheitis indecciosa (IBR), bovine viral diarrhea (BVD) and blue tongue in 1304 serum samples from cows with or without reproductive problems. The results showed the presence of antibodies to the following agents and respective percentages: ste animals positive for brucellosis (0.54%); 284 to Leptospira sp. (21.78%) for LA 776 (59.51%) for 380 RBI (29.14%) for DVB and 425 (32.59%). It was found that the agents are widespread in the herds and the association of serological results with reports of abortions showed that animals with positive serology for more than one disease had higher numbers of abortions, compared to animals with negative serology, suggesting the involvement these infectious diseases in reproductive problems. No association was found between the serological results and replays of turnover between the groups